Congenital Asplenia Interrupts Immune Homeostasis and Leads to Excessive Systemic Inflammation in Zebrafish - Xie, Lang; Chen, Zheyu; Guo, Hui; Tao, Yixi; Miao, Xiaomin; Wu, Ronghua; Li, Yun (Frontiers in Cellular and Infection Microbiology, 2021)
Splenectomy or congenital asplenia in humans increases susceptibility to infections. We have previously reported congenital asplenia in zebrafish reduces resistance to Aeromonas hydrophila infection. However, the molecular mechanism of systemic immune response in congenitally asplenic individuals is largely unexplored. In this study, we found that pro-inflammatory cytokines were more highly induced in congenitally asplenic zebrafish than wild-type after pathogenic A. hydrophila infection and LPS exposure. In addition, a higher aggregation of apoptotic cells was observed in congenitally asplenic zebrafish than that in wild-type. Next, we examined the transcriptome profiles of whole kidneys from wild-type and congenitally asplenic zebrafish to investigate the difference of innate and adaptive immune response induced by the inactivated A. hydrophila. Congenital asplenia inactivated splenic anti-inflammatory reflex, disrupted immune homeostasis and induced excessive inflammation as evidenced by the highly induced stress response related biological processes, inflammatory and apoptosis associated pathways and pro-inflammatory cytokines/chemokines in congenitally asplenic zebrafish compared with wild-type after vaccination. In addition, complement components genes (c3a.1, c3a.6, c4, c6 and c9) and several important immune-related genes (tabp.1, tap1, hamp, prg4b, nfil3, defbl1, psmb9a, tfr1a and sae1) were down-regulated in congenitally asplenic zebrafish. Furthermore, congenital asplenia impaired the adaptive immunity, as demonstrated by down-regulation of biological processes and signaling pathways that involved in adaptive immune response after vaccination in congenitally asplenic zebrafish. The expression of MHCII/IgM was also significantly reduced in the congenitally asplenic zebrafish when compared with wild-type. Together, our study provides an in-depth understanding of spleen function in controlling immune homeostasis and may help insight into pathological response in splenectomized or congenitally asplenic patients after infections.